(untitled) (Research, Society and Development, 2019)
Considering the demand for actions that strengthen attitudes towards the recovery of Guanabara Bay (GB), it is necessary to understand the resident´s perceptions about the (bay´s) environment, to develop interventions and processes in environmental education. Thus, the study analyze the environmental perception of students about GB using drawings produced by themas a methodological strategy. The research was carried out with 19 students of the 7th year of an elementary school located in Ilha do Governador. The drawings were analyzed through the principles of Content Analysis. The results show that students perceive the environment in itnatural and human aspects, and although they recognize BG as a marine environment they also made reference to the municipality in which they live by representing urban elements, which shows that f the city is also part of the GB scenario. It was also evidenced the student´s perception of the GBas a polluted environment. The relations established by the students with an environment impacted by anthropic action demonstrate that pollution and degradation strongly permeate the imaginary of the investigated students towards this space.